Roles and principles of sterilisation process in palm oil mills - Yin, Mee Thang; Yunus, Robiah; Mokhtar, Mohd Noriznan; Appleton, David Ross; Asis, Ahmad Jaril; Pei, San Kong; Huey, Fang Teh; Ariffin, Abdul Azis (Universiti Putra Malaysia Press, 2021)
Sterilisation in palm oil mills is considered a pre-treatment process as it affects stripping efficiency and oil quality. Although sterilisation technology has been well-established in the palm oil milling industry, the roles and principles of sterilisation, particularly related to the chemical changes in fruits and stalks occurring during the process, have been rarely reported. The review begins with the background literature on the biochemical properties of the FFBs, such as the compositions of binding carbohydrates and the phenomena of natural fruit detachment. Followed by the harvesting practice to understand the type of FFBs supplied to the industry. In addition, a comparison of the well-established conventional and alternative sterilisation technologies and sterilisation functions is critically reviewed and assessed. Establishing the current sterilisation process initiatives to address the natural fruit’s separation more efficiently in palm oil mills is important. Particularly visualise sterilisation as a breakup of specific binding carbohydrates that leads to strippability. It will provide a further understanding of the sterilisation mechanism, which would benefit the palm oil miller in optimising the processing of fresh fruit bunches. The information provided in this review is necessary to mitigate the percentage of unstripped bunches and reduce the oil losses and ultimately enhance the oil extraction rate.